Effect of Different Levels of Constructivist Scaffolding within E-Content on Undergraduate Students’ Mastery of Learning and their Attitudes towards it - Shemy , Nader Said (Journal of Education and e-Learning Research, 2022)
This research investigates the effect of different levels of constructivist scaffolding within e-content on undergraduate students’ mastery of learning and their attitudes towards it. The research sample involves three experimental groups, each group having thirty (30) students. The first group (Group 1) studied e-content with simple constructivist scaffolding, the second group (Group 2) studied e-content with intermediate constructivist scaffolding, the third group (Group 3) studied e-content with intensive constructivist scaffolding. The results indicate that the third group of students, who studied design skills with intensive scaffolding, scored higher than the other two groups; they achieved 85% proficiency. Though the differences are not statistically significant, the students in the other two groups did not achieve the same proficiency percentage (85%). The results further reveal that the students in the first and third groups had more positive attitudes than the students in the second group.